Idiopathic Pulmonary Haemorrhage, Is It Really Idiopathic? - Stefanie Louey; David Armstrong (Respirology Case Reports)
ABSTRACT Idiopathic pulmonary haemorrhage (IPH) is a rare cause of haemoptysis that most commonly presents in children. By definition, this condition is idiopathic in nature, however, exclusion of autoimmune capillaritis creates a diagnostic challenge. If autoimmunity is present, treatment is with immunosuppression. We present a 4‐year‐old girl with the classic clinical triad of IPH with haemoptysis, bilateral pulmonary infiltrate on chest radiography and iron deficiency anaemia. Her clinical course was complicated by frequent relapses in symptoms and critical pulmonary haemorrhage despite standard treatment for IPH. Successful remission of disease was induced with rituximab despite the absence of serological or lung biopsy evidence of autoimmune capillaritis.